Modelos pedagógicos de educación inicial subnivel II de la escuela particular Franz Giuseppe. - Artos Castellano, Estefanía Carolina (2018)
The purpose of this research is to know the different pedagogical models that are implemented in the classrooms of the private school Franz Giuseppe with the children of initial education sublevel II and to demonstrate whether it is fulfilled or not with the model that proposes of the Curriculum Initial Education 2014. The methodology for conducting the analysis and presentation of findings was qualitative: direct observation in the classroom to students and teacher, interview to teacher and director of the institution, as research tools were used daily field, observation, and questionnaire guide. In addition, a documentary analysis was conducted of the Institutional Educational Project, the Curriculum Annually and schedules of classes. In the classroom are notes that the teachers use the model constructivist as main shaft, but also focuses on other pedagogical models as the behaviorist, romantic and social-cognitive. The work presents a theoretical framework that helps to understand the problem, analysis of results, presentation of findings and conclusions.